The Nuzuli Interpretation Method (Comparative Analysis of the Books Al-Tafsir al-Hadith and Tafsir al-Qur'an al-Karim: Interpretation of Short Letters Based on the Order of Revelation) - Nanda Fatma Chamida; Idris, Idris (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the application of the nuzulī interpretation method in Kitab al-Tafsīr al-Ḥadīth by Muhammad ‘Izzat Darwazah and Tafsir al-Qur’an al-Karīm: Interpretation of Short Surahs Based on the Order of Revelation by M. Quraish Shihab. The research is motivated by the renewed scholarly interest in the nuzulī approach within contemporary Qur’anic studies, a method that arranges surahs according to the chronological order of revelation. This study employs a library research design using a comparative analytical method. The primary data sources are the two tafsir works, supported by secondary literature relevant to the topic. The findings indicate that both tafsirs are arranged based on tartīb nuzulī (chronological order of revelation). In terms of interpretive sources, both employ the bi al-iqtirān method; in their explanatory approach, they use the muqārin method; and in their elaboration, they adopt the iṭnābī method. The main difference lies in their scope: Darwazah interprets all 114 surahs, while Quraish Shihab focuses on selected thematic surahs. Therefore, al-Tafsīr al-Ḥadīth is categorized as nuzulī tajzī’ī interpretation, while Tafsir al-Qur’an al-Karīm represents the nuzulī maudū‘ī type.